2019
DOI: 10.1111/ecc.13080
|View full text |Cite
|
Sign up to set email alerts
|

Unmet supportive care needs among people with cancer: A cross‐cultural comparison between Indigenous and Non‐Indigenous Australians

Abstract: Objectives: This study describes and compares the unmet supportive care needs between Indigenous and Non-Indigenous people with cancer.Methods: Data from two cross-sectional supportive care needs studies were matched in a 1:1 ratio for Indigenous (n = 125) and Non-Indigenous (n = 125) Australian adults diagnosed with cancer. Descriptive statistics were used to compare type and prevalence of 24 need items measured by the SCNS-SF34 and SCNAT-IP. Results:A higher proportion of Non-Indigenous participants compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…These findings suggest disparities in access to services with Indigenous people accessing fewer services and these differences in access have been previously found to be associated with lower socioeconomic status and remoteness [42,43]. However, when Indigenous Australians do have access to services and are asked about their unmet supportive care needs, they indicated money worries as a frequent high unmet need [44]. This is not surprising given that many Indigenous communities live in disadvantages conditions.…”
Section: Discussionmentioning
confidence: 65%
“…These findings suggest disparities in access to services with Indigenous people accessing fewer services and these differences in access have been previously found to be associated with lower socioeconomic status and remoteness [42,43]. However, when Indigenous Australians do have access to services and are asked about their unmet supportive care needs, they indicated money worries as a frequent high unmet need [44]. This is not surprising given that many Indigenous communities live in disadvantages conditions.…”
Section: Discussionmentioning
confidence: 65%
“… 8 , 32 , 33 Previous studies involving the assessment of needs among cancer patients found that physical and psychological domains were important issues for Indigenous cancer patients. 34 , 35 …”
Section: Discussionmentioning
confidence: 99%
“…8,32,33 Previous studies involving the assessment of needs among cancer patients found that physical and psychological domains were important issues for Indigenous cancer patients. 34,35 For most Indigenous patients included in this study, the education level was Junior High school or less, and over half of the patients had at least one comorbidity (eg diabetes, hypertension and obesity). Lower education rates directly impact health literacy, and health services must adapt to the changes in patient health literacy needs.…”
mentioning
confidence: 99%
“… 33 34 Additionally, they have more limited access to definitive treatments, 32 35 have lower uptake of hospitalisations 36 and frequently have unmet supportive care needs. 37 A far lower proportion of Indigenous compared with non-Indigenous patients receive specialist palliative care at the end of life. 38 In contrast to these ‘upstream’ care disparities, the findings of the current study provide reassurance in relation to one important aspect of the care provided to Indigenous patients who access specialist palliative care services.…”
Section: Discussionmentioning
confidence: 99%